ANOTHER HYBRID CONJUGATE GRADIENT METHOD FOR UNCONSTRAINED OPTIMIZATION PROBLEMS - Koontse, M.; Kaelo, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
Conjugate gradient method is one of the most useful method for solving large scale unconstrained optimization problems. In this article a new hybrid conjugate gradient method that satisfies the descent condition independently of the line searches is proposed. In particular, it is a hybrid of the Fletcher-Reeves (β_k^FR) and Polak-Ribiere-Polyak (β_k^PRP) methods. Convergence analysis of the new method is presented. Numerical results of the method show that the proposed hybrid algorithm is just as competitive.